2020
DOI: 10.24042/ijsme.v3i1.5900
|View full text |Cite
|
Sign up to set email alerts
|

Metaphorical Thinking Berbantu Google Classroom: Pengaruhnya terhadap Kemampuan Pemahaman Konsep Matematis Siswa

Abstract: Penelitian ini bertujuan untuk mengetahui pengaruh pendekatan Metaphorical Thinking berbantuan Google Classroom terhadap peningkatan kemampuan pemahaman konsep matematis siswa SMK SWADHIPA 2 Natar. Subjek pada penelitian ini adalah siswa kelas X SMK SWADHIPA 2 Natar yang dipilih dengan teknik random sampling. Penelitian ini merupakan penelitian quasy experimental design menggunakan desain pretest-postest. Teknik pengumpulan data yang digunakan adalah tes. Pengujian hipotesis menggunakan analisis variansi satu … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
0
3
0
1
Order By: Relevance
“…For the implementation of Google Classroom in mathematics education, the results revealed that the use of Google Classroom has positively impacted learning. According to various studies, Google Classroom has enabled new experiences for students, increased their awareness of metacognition, improved their learning independence, and enhanced their understanding of mathematical concepts Susilo et al, 2019;Suryawan et al, 2021;Sundary et al, 2020;& Ari, 2020;Huda et al, 2019;Pasaribu, 2021). While most studies on the implementation of Google Classroom in mathematics education have reported positive effects on learning outcomes, a few studies did not find significant impacts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the implementation of Google Classroom in mathematics education, the results revealed that the use of Google Classroom has positively impacted learning. According to various studies, Google Classroom has enabled new experiences for students, increased their awareness of metacognition, improved their learning independence, and enhanced their understanding of mathematical concepts Susilo et al, 2019;Suryawan et al, 2021;Sundary et al, 2020;& Ari, 2020;Huda et al, 2019;Pasaribu, 2021). While most studies on the implementation of Google Classroom in mathematics education have reported positive effects on learning outcomes, a few studies did not find significant impacts.…”
Section: Discussionmentioning
confidence: 99%
“…5. (Sundary et al, 2020) The Google Classroom-assisted Metaphorical Thinking approach has an impact on improving students' understanding of mathematical concepts. 6.…”
Section: Table 2 Implementation Of Google Classroom In Mathematics Ed...mentioning
confidence: 99%
“…Mengubah pendekatan pembelajaran dari berorientasi pada guru menjadi berfokus pada peserta didik akan lebih efektif. Pendekatan ini dapat meminimalisir pembelajaran yang hanya mengandalkan hafalan tanpa pemahaman yang mendalam (Sundary, 2020). Menggunakan metode yang lebih dinamis dan beragam diharapkan dapat mengubah persepsi peserta didik terhadap matematika dari sesuatu yang sulit menjadi sesuatu yang dapat dipahami dengan baik, sehingga menciptakan prestasi yang lebih baik sesuai dengan harapan yang diinginkan.…”
Section: Pendahuluanunclassified
“…However, the competency that will be researched is limited to the understanding concept in probability lessons as the quality of concept understanding determines the learning effectiveness that needs to be considered (Afriyani, Sa'dijah, Subanji, & Muksar, 2018). Furthermore, the fundamental basis for solving the problem is that apprehending the concept underlying a problem can adopt an appropriate resolution strategy (Sundary, Jatmiko, & Widyastuti, 2020). The probability lesson, especially in combinatorics, is vital to be optimized or mastered by all grades (Ihsan & Kosasih, 2018).…”
Section: Introductionmentioning
confidence: 99%